Velocity Variation of Opak Fault GNSS Observation Station 2006 Yogyakarta Post-Earthquake - Widjajanti, Nurrohmat; Abdiana, Septi Praja; Parseno, Parseno; Pratama, Cecep (2020)
The postseismic effects of the 2006 Yogyakarta earthquake was caused by the Opak Fault activity as the possible source still continues. Secular velocity analysis who referred to the velocity which is free from the other deformations than interseismic deformation needs to be done to represent local deformation of the fault. This study was conducted to determine the significance of the difference between the secular velocity without and with postseismic corrections. The secular velocity is determined by the linear least square method. Furthermore, the velocity is calculated its postseismic correction with logarithmic method. This research data includes CORS BIG and Opak Fault station observation data from 2013 to 2018 which is processed using GAMIT/GLRED. Furthermore, the time series data for each station is plotted and analysed, then it is visualized its velocity. The result of this study shows the value of secular velocity each station range from 21.676 to 30.997 mm/year and -14.116 to. 2.573 mm/year in the East (E) and North (N) components respectively, and the resultant value of the horizontal velocities range from 22.507 to 32.711 mm/year. The secular velocity resulted with postseismic correction range from 20.735 to 29.864 mm/year and -22.255 to -6.439 mm/year in E and N components, and the resultant value of the horizontal velocities range from 36.963 to 23.281 mm/year. The velocities difference value in the E and N components range from -4.876 to 1.915 mm/year and -1.543 to 14.175 mm/year, and the horizontal velocities values range from -11.035 to 1.260 mm/year. The statistical significance of the two-parameter differences of the whole station, it is concluded that there was no significant velocities difference between the secular velocity values without and with postseismic corrections.